2011
DOI: 10.1523/jneurosci.1531-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

PDGFR  Expression Distinguishes GFAP-Expressing Neural Stem Cells from PDGF-Responsive Neural Precursors in the Adult Periventricular Area

Abstract: Jackson et al. (2006) have reported that adult glial fibrillary acid protein (GFAP)-expressing neural stem cells (NSCs) also express platelet-derived growth factor (PDGF) receptor-␣ (PDGFR␣), and that their stimulation by PDGF induced the formation of a glioma-like mass. Here, we reexamined the relationship between PDGFR␣ and GFAP expression within the three-dimensional organization of the adult periventricular area. Using four independent PDGFR␣ antibodies, we found that adult mouse GFAP-expressing NSCs and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 37 publications
6
23
0
Order By: Relevance
“…It has previously been reported that a subset of GFAP+ cells in adult mouse SVZ expresses PDGFrα (Jackson et al, 2006), suggesting the presence of SVZ GFAP+ neural precursor cells with early specification towards the oligodendroglial lineage. In contrast, Chojnacki et al (2011) reported the absence of GFAP and PDGFrα double-positive cells in the adult mouse SVZ. Employing GFAP:GFP transgenic mice allowed us to visualize GFAP+ cells and to firmly discriminate between GFAP+ and PDGFrα+ cells in the SVZ.…”
Section: Discussionmentioning
confidence: 91%
“…It has previously been reported that a subset of GFAP+ cells in adult mouse SVZ expresses PDGFrα (Jackson et al, 2006), suggesting the presence of SVZ GFAP+ neural precursor cells with early specification towards the oligodendroglial lineage. In contrast, Chojnacki et al (2011) reported the absence of GFAP and PDGFrα double-positive cells in the adult mouse SVZ. Employing GFAP:GFP transgenic mice allowed us to visualize GFAP+ cells and to firmly discriminate between GFAP+ and PDGFrα+ cells in the SVZ.…”
Section: Discussionmentioning
confidence: 91%
“…Platelet-derived growth factor (PDGF) signaling appears to play a role in balancing neuronal and oligodendrocyte production from the V-SVZ, and excessive PDGF signaling from ventricular infusion results in hyperplasia with some features of gliomas. Initial findings suggested that a significant subpopulation of cells within the hyperplasias is derived from type B1 cells (Jackson et al 2006); however, more recent work suggests that the majority, if not all, PDGF-responsive cells are oligodendroglial progenitors within the V-SVZ (Chojnacki et al 2011). Vascular endothelial growth factor (VEGF), a known angiogenic protein, also stimulates V-SVZ neurogenesis when infused into the ventricle (Jin et al 2002b), suggesting a link between angiogenesis and neurogenesis (Palmer et al 2000;Louissaint et al 2002;Greenberg and Jin 2005).…”
Section: Mitogens and Growth Factors Of The V-svzmentioning
confidence: 99%
“…Additionally, the cells should be OCT4 (POU5F1) negative; OCT4 is a pluripotency marker expressed on ESCs (Boiani and Scholer, 2005). NPCs should also be negative for GFAP (astrocytes), PDGFRalpha (oligodendrocytes) and MAP2 (neurons), as this would indicate further differentiation and loss of multipotency (Chojnacki et al, 2011; Jacque et al, 1978; Shafit-Zagardo and Kalcheva, 1998). …”
Section: Basic Protocol 1: Preparation Of Hnpcs For Mouse Intraspinalmentioning
confidence: 99%